2017
DOI: 10.1073/pnas.1619582114
|View full text |Cite
|
Sign up to set email alerts
|

Folate rescues vitamin B 12 depletion-induced inhibition of nuclear thymidylate biosynthesis and genome instability

Abstract: Clinical vitamin B deficiency can result in megaloblastic anemia, which results from the inhibition of DNA synthesis by trapping folate cofactors in the form of 5-methyltetrahydrofolate (5-methylTHF) and subsequent inhibition of de novo thymidylate (dTMP) biosynthesis. In the cytosol, vitamin B functions in the remethylation of homocysteine to methionine, which regenerates THF from 5-methylTHF. In the nucleus, THF is required for de novo dTMP biosynthesis, but it is not understood how 5-methylTHF accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 52 publications
5
38
0
1
Order By: Relevance
“…In both A549 and T.T cells, MTR is essential for proliferation when 5methyl THF is the sole folate source ( Figure 2B-C). MTR knockout cells display high steadystate levels of 5-methyl THF regardless of folate source ( Figure 2D-E), consistent with previous results 27 . This trapping of folate as 5-methyl THF in the MTR knockout cells may explain the small decrease in proliferation observed in A549 MTR knockout cells compared to EV control cells when cultured in folic acid.…”
Section: Resultssupporting
confidence: 92%
“…In both A549 and T.T cells, MTR is essential for proliferation when 5methyl THF is the sole folate source ( Figure 2B-C). MTR knockout cells display high steadystate levels of 5-methyl THF regardless of folate source ( Figure 2D-E), consistent with previous results 27 . This trapping of folate as 5-methyl THF in the MTR knockout cells may explain the small decrease in proliferation observed in A549 MTR knockout cells compared to EV control cells when cultured in folic acid.…”
Section: Resultssupporting
confidence: 92%
“…Metabolically, both folate and vitamin B 12 are required for nucleic acid synthesis and methyl group generation, and are linked through the remethylation of Hcy to methionine. 13 Vitamin B 12 deficiency will inhibit DNA synthesis by trapping folate as 5-methyltetrahydrofolate, 24 and reduction of mitochondrial DNA in obese people is considered to be associated with insulin resistance. 25 Recent studies revealed that folic acid could play a role in the development of diabetes via natural killer cell dysfunction, 26 and low vitamin B 12 levels in pregnancy alter adipose-derived circulating microRNAs, which may mediate an adipogenic and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the close biochemical relationship between folate and vitamin B 12 , it is biologically plausible that, among individuals with low vitamin B 12 status, those with different underlying folate status could have different short‐term responses to injections of vitamin B 12 . It is well established in the literature that elevated intake of folate or folic acid can functionally compensate for vitamin B 12 deficiency, as first reported for the masking of vitamin B 12 deficiency–related megaloblastic anemia by folic acid . Hence, vitamin B 12 ‐deficient individuals with elevated folate status would be expected to exhibit less improvement in functional indicators as a result of vitamin B 12 therapy than those with lower folate status because of the functional compensation afforded by folate in vitamin B 12 deficiency.…”
Section: Safety Of Folic Acidmentioning
confidence: 99%
“…However, elevated folic acid intake is not known to rescue neurological pathology resulting from vitamin B 12 deficiency. There are no proposed biological premises or suggested mechanisms whereby elevated folic acid intake exacerbates vitamin B 12 deficiency at the level of metabolism, cellular physiology, or human pathogenesis …”
Section: Safety Of Folic Acidmentioning
confidence: 99%
See 1 more Smart Citation